Lithium iron phosphate positive electrode material and preparation method and application thereof
By sintering treatment under high-pressure organic gas environment, the problem of Fe3+ reduction effect and uneven carbon coating of lithium iron phosphate positive electrode material is solved, the electrochemical performance and charging and discharge energy of the material are improved, and more efficient lithium iron phosphate positive electrode is achieved. Material preparation.
Patent Information
- Application Number
- CN202411341250.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-31
AI Technical Summary
In the prior art, the Fe3+ reduction effect of the lithium iron phosphate positive electrode material is not ideal and the carbon coating is uneven, resulting in poor specific capacity of the material and it is difficult to optimize on the basis of simple process.
Sintering is carried out in an organic gas environment with a relative pressure of ≥1MPa, and the organic gas is cracked under high pressure to generate H2, thereby achieving reduction of Fe3+ and forming a uniform carbon cladding layer.
It significantly improves the charge and discharge energy and electrochemical properties of lithium iron phosphate materials, reduces the resistivity, and improves the uniformity of carbon coating.
Smart Images

Figure CN119218957A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium iron phosphate positive electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have been widely used in all aspects of our lives due to their high energy and long life performance advantages. Lithium-ion batteries can be divided into three categories according to the usage scenario and energy size: lithium power batteries, lithium consumer batteries and lithium energy storage batteries. At present, lithium power batteries mainly use lithium iron phosphate and nickel-cobalt-manganese ternary materials as positive electrode materials. Among them, although nickel-cobalt-manganese ternary materials have the advantages of high energy density and good cycle performance, their material cost is relatively high due to the presence of precious metals such as Ni and Co, and they are generally used in high-end electric vehicles. Lithium iron phosphate has low raw material cost and abundant resources. Although its energy density is relatively low, it is more competitive in terms of cost and can provide more affordable vehicles for the middle class. Therefore, it is selected by more and more car companies, and its market share is rising steadily.
[0003] There are many methods for preparing lithium iron phosphate, among which the most common ones are high-temperature solid phase method, sol-gel method, chemical precipitation method, etc. At present, the industry generally adopts high-temperature solid phase method to prepare lithium iron phosphate. In the process of synthesizing lithium iron phosphate by traditional high-temperature solid phase method, carbon source is generally used to react with Fe 3+ However, the carbon coating effect of synthesizing lithium iron phosphate by this method is poor and has a negative impact on Fe 3+ The reduction effect is not ideal, which leads to poor specific capacity of the prepared lithium iron phosphate material. 3+ The reduction degree and carbon coating effect are optimized one by one to obtain lithium iron phosphate materials with better electrochemical performance, but the operation steps are relatively complicated. Based on the design principle of simple process, how to improve Fe 3+ There has been no public report on how to achieve a reduction effect while solving the problem of uneven carbon coating on the surface of solid carbon-coated lithium iron phosphate. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the problem that the prior art does not disclose how to increase Fe 3+ The reduction effect is improved while solving the defect of uneven carbon coating on the surface of solid-phase carbon-coated lithium iron phosphate, thereby providing a lithium iron phosphate positive electrode material and a preparation method and application thereof that solve the above problem.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] A method for preparing a lithium iron phosphate positive electrode material comprises: placing a lithium iron phosphate material coated with solid carbon in an organic gas environment with a relative pressure of ≥1 MPa and performing a sintering treatment to obtain the material.
[0007] Preferably, the relative pressure is 1-10 MPa;
[0008] And / or, the sintering temperature is 650-850°C;
[0009] And / or, the sintering treatment time is 10-12h;
[0010] And / or, the organic gas is methane and / or ethane;
[0011] And / or, the sintering process is followed by a pulverizing process.
[0012] Preferably, the preparation method of the solid-phase carbon-coated lithium iron phosphate material comprises: blending a lithium source with iron phosphate, a carbon source, and a solvent and drying the mixture to obtain a first precursor;
[0013] The first precursor is obtained by pre-sintering.
[0014] Preferably, the lithium source is lithium carbonate;
[0015] And / or, the carbon source is glucose and / or sucrose;
[0016] And / or, the solvent is pure water.
[0017] Preferably, the molar ratio of lithium element to iron phosphate in the lithium source is (1-1.05):1;
[0018] and / or, the molar ratio of the carbon source to the iron phosphate is 0.2:10; in the solid phase carbon coating, there is no clear addition ratio range for carbon;
[0019] And / or, based on 10 mol of iron phosphate, the amount of the solvent is 500-1000 g.
[0020] Preferably, the blending process is ball milling and / or sand milling;
[0021] And / or, the drying process is spray drying.
[0022] Preferably, the inlet temperature of the spray drying is 160-200°C;
[0023] And / or, the outlet temperature of the spray drying is 120-140°C;
[0024] And / or, the spray drying atmosphere is an inert atmosphere.
[0025] Preferably, the temperature of the pre-sintering treatment is 450-550°C;
[0026] And / or, the duration of the pre-sintering treatment is 1-4 hours;
[0027] And / or, the atmosphere of the pre-sintering treatment is an inert atmosphere.
[0028] The present invention also provides a lithium iron phosphate positive electrode material, which is prepared by the above-mentioned method for preparing the lithium iron phosphate positive electrode material.
[0029] The present invention also provides application of the lithium iron phosphate positive electrode material in a lithium ion battery.
[0030] In the present invention, the inert atmosphere is nitrogen and / or argon.
[0031] In the present invention, the relative pressure is the vacuum gauge pressure, that is, the actual internal pressure-the atmospheric pressure=the relative pressure.
[0032] The technical solution of the present invention has the following advantages:
[0033] A method for preparing a lithium iron phosphate positive electrode material comprises: placing a solid carbon-coated lithium iron phosphate material in an organic gas environment with a relative pressure of ≥1 MPa and sintering the material. In the synthesis process of lithium battery material LiFePO4, the industry often uses a slightly positive pressure (to prevent air from entering the furnace) for sintering, but the carbon coating of the solid carbon-coated lithium iron phosphate material is uneven, and in a slightly positive pressure environment, it is difficult for the reducing gas to remove the Fe in the bulk phase and the core of the particles. 3+ Reduction to Fe 2 + In this regard, the present invention performs cracking and carbonization of organic gas under high pressure to generate H2 and carbon. The generated H2 can convert Fe in the solid carbon-coated lithium iron phosphate material under high pressure. 3+ Reduction to Fe 2+ , a purer lithium iron phosphate material is obtained, and the generated carbon single substance is densely and evenly adsorbed on the surface of the material, thereby forming a uniform carbon coating layer on the surface of the solid carbon-coated lithium iron phosphate material. + After deintercalation, Fe x+ Transformed into Fe 3+ ) It can be seen that the lower the Fe valence state in LiFePO4, the more electrons can be lost, the more lithium ions can be deintercalated, and the more energy the material obtains. Based on this, the use of this method can effectively improve the charge and discharge energy of lithium iron phosphate materials. Combining the above technical means, the present invention can effectively improve the charge and discharge energy of Fe 3+While achieving the reduction effect, the problem of uneven carbon coating on the surface of solid-phase carbon-coated lithium iron phosphate is solved, and the resistivity of the prepared lithium iron phosphate material is significantly reduced, and the electrochemical performance of the lithium iron phosphate material is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0035] Figure 1 It is a cycle performance diagram of the lithium iron phosphate positive electrode material prepared in the embodiment of the present invention and the comparative example. DETAILED DESCRIPTION
[0036] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0037] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0038] Example 1
[0039] This embodiment provides a method for preparing a lithium iron phosphate positive electrode material, and the specific steps are as follows:
[0040] 1) 5 mol Li2CO3, 10.0 mol FePO4, 0.2 mol glucose and 500 g pure water were ball-milled, pumped into a spray drying device with an inlet temperature of 180° C. and an outlet temperature of 130° C., and spray-dried in a nitrogen atmosphere to obtain a first precursor;
[0041] 2) placing the first precursor obtained in step 1) in a nitrogen atmosphere and sintering at 500° C. for 2 h to obtain a solid-phase carbon-coated lithium iron phosphate material;
[0042] 3) The solid carbon-coated lithium iron phosphate material obtained in step 2) is placed in a high-pressure sintering furnace, introduced into a methane atmosphere and a relative pressure of 10 MPa, sintered at 750° C. for 10 h, and finally pulverized to obtain a LiFePO4 positive electrode material.
[0043] Example 2
[0044] This embodiment provides a method for preparing a lithium iron phosphate positive electrode material, and the specific steps are as follows:
[0045] 1) After ball milling 5 mol Li2CO3, 10.0 mol FePO4, 0.2 mol glucose and 500 g pure water, the mixture was pumped into a spray drying device with an inlet temperature of 160° C. and an outlet temperature of 120° C., and spray dried in a nitrogen atmosphere to obtain a first precursor;
[0046] 2) placing the first precursor obtained in step 1) in a nitrogen atmosphere and sintering at 450° C. for 4 hours to obtain a solid-phase carbon-coated lithium iron phosphate material;
[0047] 3) The solid carbon-coated lithium iron phosphate material obtained in step 2) is placed in a high-pressure sintering furnace, introduced into an ethane atmosphere and sintered at 650° C. for 12 h under a relative pressure of 10 MPa, and finally pulverized to obtain a LiFePO4 positive electrode material.
[0048] Example 3
[0049] This embodiment provides a method for preparing a lithium iron phosphate positive electrode material, and the specific steps are as follows:
[0050] 1) 5.2 mol Li2CO3, 10.0 mol FePO4, 0.2 mol sucrose and 1000 g pure water were ball-milled, pumped into a spray drying device with an inlet temperature of 200° C. and an outlet temperature of 140° C., and spray-dried in a nitrogen atmosphere to obtain a first precursor;
[0051] 2) placing the first precursor obtained in step 1) in a nitrogen atmosphere and sintering at 550° C. for 1 h to obtain a solid-phase carbon-coated lithium iron phosphate material;
[0052] 3) The solid carbon-coated lithium iron phosphate material obtained in step 2) is placed in a high-pressure sintering furnace, introduced into a methane atmosphere and 1 MPa relative pressure, sintered at 850° C. for 10 h, and finally pulverized to obtain a LiFePO4 positive electrode material.
[0053] Comparative Example 1
[0054] This comparative example provides a method for preparing a lithium iron phosphate positive electrode material, and the specific steps are as follows:
[0055] 1) 5 mol Li2CO3, 10.0 mol FePO4, 0.2 mol glucose and 500 g pure water were ball-milled, pumped into a spray drying device with an inlet temperature of 180° C. and an outlet temperature of 130° C., and spray-dried in a nitrogen atmosphere to obtain a first precursor;
[0056] 2) placing the first precursor obtained in step 1) in a nitrogen atmosphere and sintering at 500° C. for 2 h to obtain a solid-phase carbon-coated lithium iron phosphate material;
[0057] 3) The solid carbon-coated lithium iron phosphate material obtained in step 2) is placed in a roller kiln commonly used for sintering (it can only be sintered under normal atmospheric pressure. If the pressure needs to be increased, the amount of gas must be increased. After the amount of gas is increased, the temperature cannot be maintained at a constant temperature of 750°C. Moreover, its structure cannot support a relative pressure of 1Mpa), and a methane atmosphere and a relative pressure of 0.2MPa are introduced. It is sintered at 750°C for 10 hours, and finally crushed to obtain a LiFePO4 positive electrode material.
[0058] Comparative Example 2
[0059] This comparative example provides a method for preparing a lithium iron phosphate positive electrode material, and the specific steps are as follows:
[0060] 1) 5 mol Li2CO3, 10.0 mol FePO4, 0.2 mol glucose and 500 g pure water were ball-milled, pumped into a spray drying device with an inlet temperature of 180° C. and an outlet temperature of 130° C., and spray-dried in a nitrogen atmosphere to obtain a first precursor;
[0061] 2) The first precursor obtained in step 1) is placed in a nitrogen atmosphere and sintered at 500° C. for 2 h to obtain a solid carbon-coated lithium iron phosphate material, which is then crushed to obtain a LiFePO4 positive electrode material.
[0062] Comparative Example 3
[0063] This comparative example provides a method for preparing a lithium iron phosphate positive electrode material, and the specific steps are as follows:
[0064] 1) 5 mol Li2CO3, 10.0 mol FePO4, 0.2 mol glucose and 500 g pure water were ball-milled, pumped into a spray drying device with an inlet temperature of 180° C. and an outlet temperature of 130° C., and spray-dried in a nitrogen atmosphere to obtain a first precursor;
[0065] 2) placing the first precursor obtained in step 1) in a nitrogen atmosphere and sintering at 500° C. for 2 h to obtain a solid-phase carbon-coated lithium iron phosphate material;
[0066] 3) The solid carbon-coated lithium iron phosphate material obtained in step 2) is added to 10000 mL of a solution containing 5.1 g of methyl cellulose to form a stable slurry, and the slurry is ball-milled in a stirring mill at a ball-to-material ratio of 1:5 and a ball milling rate of 800 r / min for 7 h, followed by atomization drying, and then placed in a high-pressure sintering furnace, introduced into a nitrogen atmosphere and a relative pressure of 10 MPa, sintered at 650 ° C for 12 h, and finally pulverized to obtain a LiFePO4 positive electrode material.
[0067] Test Example 1
[0068] The resistivity and electrochemical performance of the LiFePO4 positive electrode materials prepared in the examples and comparative examples were tested.
[0069] The conductivity test method is as follows: after grinding the final products of the embodiment and the comparative example through a 325-mesh sieve, 1.00 g of the sample is weighed with weighing paper, the sample is placed in a sample holder, compacted under a pressure of 10 MPa, and tested with an FT-7200A automatic four-probe powder resistivity tester. The resistivity test results of the compacted material are shown in Table 1 below.
[0070] Electrochemical performance test: lithium iron phosphate material, carbon black and PVDF were weighed and mixed in a mass ratio of 8:1:1, and the positive electrode slurry was prepared after adding the solvent NMP. The slurry was evenly coated on the aluminum foil and baked at 105°C for 2h. The baked electrode was cut and placed in a tablet press for compaction at 25Mpa. Small discs were cut out and assembled under a nitrogen atmosphere, in which the water vapor and oxygen content were less than 0.1ppm. The small discs were placed on the positive side of the button battery housing with the fluorine-coated side facing the positive electrode, and 50μL of 1mol / L electrolyte (EC, DMC and EMC in a volume ratio of 1:1:1) was dripped in, a diaphragm was placed in and 50μL of electrolyte was dripped in, a pure lithium sheet, a gasket, and a shrapnel were placed in the button battery negative electrode housing, and the battery was packaged into a CR2032 button battery. The charging and discharging system is as follows: the charging cut-off voltage is 4.3V, and the discharging cut-off voltage is 3.0V; the first cycle is 0.2C charging and 0.2C discharging; the second cycle is 0.5C charging and 0.5C discharging; the third cycle is 1.0C charging and 1.0C discharging; then the cycle retention rate is tested by 200 cycles of 1C charging and 1C discharging. The test results are shown in Table 1 and Figure 1 shown.
[0071] Table 1
[0072]
[0073]
[0074] According to the above test results, compared with comparative examples 1-3, the resistivity of the positive electrode material prepared in the embodiment of the present invention is significantly reduced, and the electrochemical performance of the lithium iron phosphate material is significantly improved.
[0075] Further analysis of the reasons for the above test results: In Example 1, low-pressure methane cracking was performed, but methane could not be cracked at low pressure, the reaction kinetics was not enough (the methane cracking temperature at normal pressure was above 800°C), and no methane was cracked to produce H2 and carbon, and the Fe in the material could not be removed. 3+ Reduction to Fe 2+ , Li x FePO4 is a Li-deficient phase, and the carbon coating on the surface of the material is still uneven and incomplete, with low conductivity, which in turn affects the electrical performance, resulting in low capacity and poor cycle of the material.
[0076] Comparative Example 2 did not perform high-pressure methane cracking, and there was no H2 generation, so the Fe 3+ Reduction to Fe 2+ , Li x FePO4 is a Li-deficient phase, and the carbon coating on the surface of the material is uneven and incomplete, with low conductivity, which in turn affects the electrical performance, resulting in low capacity and poor cycle of the material.
[0077] In Comparative Example 3, methyl cellulose is coated on the surface of solid carbon-coated lithium iron phosphate material for modification. However, methyl cellulose is pyrolyzed at high temperature under high-pressure nitrogen atmosphere to generate H2O and CO2, without generating carbon element or H2. Therefore, the obtained material has poor conductivity, low capacity and poor cycle.
[0078] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for preparing a lithium iron phosphate positive electrode material, characterized in that: include: The solid carbon-coated lithium iron phosphate material is placed in an organic gas environment with a relative pressure of ≥1 MPa and sintered.
2. The preparation method according to claim 1, characterized in that: The relative pressure is 1-10MPa; And / or, the sintering temperature is 650-850°C; And / or, the sintering treatment time is 10-12h; And / or, the organic gas is methane and / or ethane; And / or, the sintering process is followed by a pulverizing process.
3. The preparation method according to claim 1 or 2, characterized in that: The preparation method of the solid-phase carbon-coated lithium iron phosphate material comprises: blending a lithium source with iron phosphate, a carbon source, and a solvent and drying the mixture to obtain a first precursor; The first precursor is obtained by pre-sintering.
4. The preparation method according to claim 3, characterized in that: The lithium source is lithium carbonate; And / or, the carbon source is glucose and / or sucrose; And / or, the solvent is pure water.
5. The preparation method according to claim 3 or 4, characterized in that: The molar ratio of lithium element to iron phosphate in the lithium source is (1-1.05):1; And / or, based on 10 mol of iron phosphate, the amount of the solvent is 500-1000 g.
6. The preparation method according to any one of claims 3 to 5, characterized in that: The blending process is ball milling and / or sand milling; And / or, the drying process is spray drying.
7. The preparation method according to claim 6, characterized in that: The inlet temperature of the spray drying is 160-200°C; And / or, the outlet temperature of the spray drying is 120-140°C; And / or, the spray drying atmosphere is an inert atmosphere.
8. The preparation method according to any one of claims 3 to 7, characterized in that: The temperature of the pre-sintering treatment is 450-550°C; And / or, the duration of the pre-sintering treatment is 1-4 hours; And / or, the atmosphere of the pre-sintering treatment is an inert atmosphere.
9. A lithium iron phosphate positive electrode material, characterized in that: The lithium iron phosphate positive electrode material is prepared by the method for preparing the lithium iron phosphate positive electrode material according to any one of claims 1 to 8.
10. Use of the lithium iron phosphate positive electrode material according to claim 9 in lithium ion batteries.